Predictive factors of mortality in ruptured hepatocellular carcinoma - P. Mahawithitwong (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2020 Background: Ruptured hepatocellular carcinoma (HCC) globally carries a high mortality rate. In Thailand, the incidence of ruptured HCC remains high and the data is still lacking. This study aims to identify the predictive factors of death in these patients. Materials and methods: This study is a retrospective review of 4,330 patients diagnosed with HCC admitted at Siriraj Hospital from January 2012 to June 2018. Forty-five patients diagnosed with ruptured HCC were included in this study. The patients were divided into a survivor group and a mortality group. Demographic data, clinical manifestations, biochemical data, tumor characteristics, and therapeutic procedures were collected. The mortality rate and factors associated with mortality were analyzed. Results: 10 patients and 35 patients were categorized in the survivor group and the mortality group, respectively. Demographic data between the two groups were comparable. Emergency hemostasis was achieved with transarterial embolization (TAE) in 40% of survivor group and 65% of mortality group. In survivor group, hepatectomy could be achieved in 80% of the patients. The multivariate analyses found that the predictive factors of death in ruptured HCC were the inability to undergo further definitive hepatectomy (p = 0.04) and high serum creatinine level (p = 0.01). Overall survival of ruptured HCC patients at 1-month, 1-year, and 3-year were 76.0%, 26.4%, 13.2%, respectively. Overall survival after hepatectomy at 1-month, 1-year, and 3-year were 100%, 100% and 75%, respectively. Conclusion: The predictive factors of death in ruptured HCC patients were the inability to undergo further hepatectomy and high serum creatinine level. Patients who underwent hepatectomy as a definitive treatment could achieve a better survival outcome after ruptured HCC.